СУЧАСНІ ПІДХОДИ ДО ПРОЕКТУВАННЯ ТА ОРГАНІЗАЦІЇ БАЗИ ДАНИХ ДЛЯ ТЕХНОЛОГІЧНИХ КАРТ НА ПІДПРИЄМСТВАХ РЕСТОРАННОГО БІЗНЕСУ (Development Service Industry Management, 2025)
MODERN APPROACHES TO DESIGNING AND ORGANIZING A DATABASE FOR TECHNOLOGICAL MAPS AT RESTAURANT ENTERPRISES SHULLA Roman, POPYK MarianaUzhhorod National University The article demonstrates that relational databases represent an effective tool for organizing an enterprise’s information system, as they allow for the optimal structuring of relevant economic information concerning technological charts in the restaurant industry. It is substantiated that the key advantage of using databases lies in eliminating redundant duplication of information during its initial registration or modification within the enterprise’s information system. The study proves that efficient database design for technological charts (dish component structures) in restaurant enterprises requires a scientifically grounded approach, which includes three stages: designing the data structure at the conceptual level, designing the data structure with consideration of the properties of a specific DBMS, and applying a programming language to describe the data structure in accordance with the specific DBMS. The advantages of using ER-models in the design of databases for technological charts in restaurant enterprises are justified, as they allow for a comprehensive consideration of all relevant information objects in a given applied domain and the interrelations among them. The necessity of forming a database for the component structure of products in the restaurant industry based on the concept of a comprehensive oriented graph is demonstrated. This approach ensures that individual structural components of dishes are recorded in the database only once. It is substantiated that for the accurate representation of information regarding technological charts and the corresponding component structure of dishes in restaurant enterprises, the implementation of a two-table relational system is required, consisting of "Material Objects" and "Structural Interrelations between Material Objects," characterized by a recursive type of relationship. In this framework, the "Material Objects" table should contain information on final products, semi-finished goods, and purchased materials, while the "Structural Interrelations between Material Objects" table should specify data on the consumption norms of material resources per unit of product or semi-finished good. The advantages of implementing the database of dish component structures in the "MS Access" DBMS environment are also substantiated.Keywords: database, DBMS, relational model, ER-model, restaurant business, dish component structure, technological chart.
Keywords: database; DBMS; relational model; ER-model; restaurant business; dish component structure; technological chart